ISOLASI SELULOSA DARI SERAT SABUT KELAPA (Cocos nucifera L.) PADA VARIASI SUHU DAN WAKTU PROSES BLEACHING DENGAN ASAM PERASETAT - Santhi, Manika; Arnata, I Wayan; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 3 (2022): September, 2022)
Cellulose is a chemical component of lignocellulose that can be found in most cell walls and woody parts of plants. One of the plants that has a high cellulose content is coco fiber, which is 43.44%. However, the potential of cellulose  content  in coco fiber is still not optimally utilized. This study aims to determine the effect of the temperature and time of the  bleaching  process using peracetic acid (PA) on the characteristics of the cellulose produced, as well as to determine the best combination of temperature and time for the  bleaching  process with PA to produce coco fiber cellulose. This study used a randomized block design with two factors, that were temperature (60°C, 80°C, and 100°C) and time (30 minutes and 60 minutes). Data were analyzed by analysis of variance and continued with Duncan's multiple comparison test. Variables observed were yield, degree of whiteness, content of cellulose, hemicellulose,  and  lignin. The results showed that the treatment temperature and time of the  bleaching  process using PA had a significant effect on all observed variables. The interaction between temperature and time of the  bleaching  process had a significant effect on whiteness, cellulose, hemicellulose, and lignin content, but did not significantly affect the yield content of coco fiber. The best treatment to produce cellulose was obtained by using PA at a temperature of 100°C and a time of 60 minutes. The characteristics were 35.38±0.32% yield, 84.77±0.81% degree of whiteness, 83.14±0.22% cellulose, 6.60±0.51% hemicellulose,  and 4.23±0.55% lignin.